A bidirectional cohort study to compare the outcomes of transperitoneal and retroperitoneal approaches in subjects undergoing laparoscopic live donor nephrectomy - S., Praveena; Krishnamoorthy, Venkatesh; Tyagaraj, Krishnaprasad (Current urology, 2025)
Abstract Background Laparoscopic transperitoneal donor nephrectomy (LTDN) is currently the standard procedure for renal donation from living donors. Only a handful of clinical studies have compared the outcomes of retroperitoneoscopic donor nephrectomy (RDN) and LTDN. More robust data and systematic comparative analyses of the outcomes and complications of these 2 techniques are needed. This study aimed to elucidate the noninferiority of RDN to LTDN. Materials and methods All live renal donors who underwent either RDN or LTDN at our institution during the period of January 2015 to March 2021 were considered subjects, excluding those who refused to participate in the study. This was a bidirectional cohort study. Demographic and clinical data were collected and analyzed using standard statistical methods. Statistical significance was set at p < 0.05. Results Our study included 89 subjects: 40 in the LTDN group and 49 in the RDN group. The RDN group had significantly shorter warm ischemia time (2.85 vs. 6.04 minutes), a lower fall in hemoglobin on postoperative day (POD)-1 (1.73 vs. 2.24 g/dL), lower estimated blood loss (601.93 vs. 797.27 mL), and lower pain on POD-1 (0.78 vs. 1.28). The improvement in recipient's estimated glomerular filtration rate on POD-30 was significantly higher in the RDN group (79.98 vs. 63.73 mL/min/1.73 m2). There was a significantly higher fall in estimated glomerular filtration rate of donor after nephrectomy in RDN group on POD-30 (35.53 vs. 30.60 mL/min/1.73 m2). However, there were no significant differences in other parameters. Conclusions Our study, conducted in India, showed that the majority of RDN outcomes were better than those of LTDN. Hence, RDN is clearly non-inferior to the gold standard LTDN. A well-designed randomized controlled study is required to elucidate the statistical superiority of one approach over another.